PEMODELAN MATEMATIKA: MODEL DAN SIMULASI JALUR EVAKUASI KORBAN BENCANA GEMPA BUMI DI BANGUNAN BERTINGKAT - R. Radiusman; A. Fauzi; M. A. Maulyda; A. Widodo; M. Simajuntak (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kristen Indonesia, 2020)
The post-disaster evacuation process is something that must be done to minimize casualties. The process of evacuation should get the attention that more than the government and society. Often the process of evacuation was not done with good, so that raises some problems such as the slow evacuation, the buildup of victims in the evacuation route and increasing casualties due to slow handling. In the case of the earthquake, often found some victims do not evacuate and trapped in the rubble. Seeing the fact that, the process of evacuation of victims of the earthquake the Earth needs to be planned by well so that the evacuation can be done with good. The research is discussed about the development model of the evacuation of victims of the disaster earth on building multi-story. The stages of research begin with doing the characterization system. The next stage is the process of developing a mathematical model. After the model is developed, the method of achieving the model solution is further developed. The final stage of this research is the analysis of the model and concluding. The model is produced in the research is expected to result in a solution that is good and right for the evacuation of victims of the disaster earth on building multi-story.